2018
DOI: 10.1128/aac.01788-17
|View full text |Cite
|
Sign up to set email alerts
|

Drug Susceptibility Profiling and Genetic Determinants of Drug Resistance in Mycobacterium kansasii

Abstract: Very few studies have examined drug susceptibility of , and they involve a limited number of strains. The purpose of this study was to determine drug susceptibility profiles of isolates representing a spectrum of species genotypes (subtypes) with two different methodologies, i.e., broth microdilution and Etest assays. To confirm drug resistance, drug target genes were sequenced. A collection of 85 isolates, including representatives of eight different subtypes (I to VI, I/II, and IIB) from eight countries, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
33
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 46 publications
6
33
1
1
Order By: Relevance
“…The INH and ETO MICs were low, and within relatively narrow ranges (<0.25-2 mg/L vs. <0.3-0.6 mg/L). These findings confirm the key observations from previous studies, on the susceptibility of M. kansasii strains to RIF and their high resistance to EMB (da Silva Telles et al, 2005;Wu et al, 2009;Shahraki et al, 2017;Bakuła et al, 2018c). This, confronted with the ATS recommendation of a three-drug (INH-RIF-EMB) regimen for the treatment of M. kansasii disease, speaks for exclusion of EMB and its replacement with other potent drug, such as moxifloxacin.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The INH and ETO MICs were low, and within relatively narrow ranges (<0.25-2 mg/L vs. <0.3-0.6 mg/L). These findings confirm the key observations from previous studies, on the susceptibility of M. kansasii strains to RIF and their high resistance to EMB (da Silva Telles et al, 2005;Wu et al, 2009;Shahraki et al, 2017;Bakuła et al, 2018c). This, confronted with the ATS recommendation of a three-drug (INH-RIF-EMB) regimen for the treatment of M. kansasii disease, speaks for exclusion of EMB and its replacement with other potent drug, such as moxifloxacin.…”
Section: Resultssupporting
confidence: 89%
“…**Results according to Shahraki et al (2017). ***Results according to Tagini et al (2019 Please note, that for some isolates those data were reported elsewhere (Bakuła et al, 2018c). a According to the WGS-based (MiSI method) grouping.…”
Section: Resultsmentioning
confidence: 91%
“…Except ethambutol (83.87% vs 20.5%), the resistant rate in our study is lower than previous study, clarithromycin (0 vs 20.5%), amikacin (0 vs 5.1%), rifampicin (6.45% vs 56.4%), rifabutin (3.23%% vs 34.6%), moxi oxacin (0 vs 16.7%) and linezolid (3.23%% vs 32.1%). Our result is similar with a report which used 85 M. kansassi obtained from 8 countries in Europe and Asia [37]. All isolates tested in that study were susceptible to rifampicin, amikacin, rifabutin, moxi oxacin, and linezolid.…”
Section: Discussionsupporting
confidence: 92%
“…In another report on ciprofloxacin-resistant isolates from South Korea, 12 M. abscessus isolates and 17 M. massiliense isolates had no DNA gyrase gene mutations (24). In addition, a recent study from Poland reported that 17 ciprofloxacinresistant M. kansasii isolates did not harbor any changes in gyrA or gyrB (31).…”
mentioning
confidence: 96%